Counterfeiting as a monetary factor influencing the inflation rate - A. S. Shelupakhin; I. O. Kuznetsov (Путеводитель предпринимателя, 2021)
The article presents the results of the study of counterfeiting as one of the monetary factors influencing the inflation rate. The essence of the concept of «counterfeiting» is revealed, its concept is considered.